Influence of Work Abilities and Work Environment on Employee Performance in the Archives and Library Services of Paser District - Sari, Widiya Ratna; Wahiyuddin, La Ode; Rosita, Tita (Pancasila International Journal of Applied Social Science, 2024)
Civil Servant (PNS) Performance Assessment has been regulated in PP no 30 of 2019. The results of the evaluation of the performance accountability system at the Archives and Libraries Office show that the performance achievement of the Paser District Archives and Libraries Office during 2019 and 2020 has decreased. The purpose of this study was to analyze the effect of work ability and work environment on the performance of employees of the Paser Regency Archives and Libraries Office. The research design used is mix methods. In this mixed methods study, a sequential explanatory type was used, namely describing quantitative data first and then strengthening it with qualitative data. The population in this study were all employees at the Paser Regency Archives and Libraries Office, consisting of 50 civil servants and PTTs. The sampling technique in this study uses total sampling because the population is small. In this study, researchers used two research instruments, namely a questionnaire and a structured list of questions. The results of the calculation of the partial test between work ability on employee performance from the coefficient table obtained a significance value of 0.24, it can be concluded that the work ability variable has a significant positive effect on performance. The results of the calculation of the partial test between the work environment on employee performance from the coefficient table obtained a significance value of 0.01, it can be concluded that the regression coefficient of the work environment variable has a significant effect on employee performance. It is hoped that agency leaders can rotate each of their employees in participating in the training, so that all employees can develop their skills and talents to support their work. It is necessary to carry out a physical evaluation of rooms, infrastructure that can no longer support employee performance so that they can be replaced, equipped and held immediately